Effect of epigallocatechin gallate on gene expression of Staphylococcus aureus. (September 2020) - Kitichalermkiat, Apisada; Katsuki, Mao; Sato, Jun; Sonoda, Takumi; Masuda, Yoshimitsu; Honjoh, Ken-ichi; Miyamoto, Takahisa
Highlights: EGCg upregulated transcription of genes involved in membrane transport. EGCg downregulated transcription of genes involved in toxin production and stress response. Staphylococcus aureus cells largely decreased membrane potential in the presence of EGCg. Abstract: Objectives: Staphylococcus aureus is an important nosocomial pathogen that produces various extracellular toxins. Epigallocatechin gallate (EGCg) is a polyphenol that is abundant in green tea. EGCg displays strong antibacterial activity against Gram-positive bacteria. The effect of EGCg on gene expression by S. aureus was investigated to clarify the mechanism underlying its antibacterial action. Methods: Microarray analysis was performed on S. aureus treated with or without 500 mg/L EGCg. Differentially expressed genes were identified and their changes at the transcription level were confirmed using real-time quantitative polymerase chain reaction (qPCR). The membrane potential of cells treated with or without EGCg were observed under fluorescence microscopy. Results: Microarray analysis revealed that EGCg treatment of S. aureus resulted in increased and decreased transcription of 75 and 72 genes, respectively. Increased transcription exceeding 1-log2 -fold change of genes related to membrane transport included gntP, gntK, rumA, SAOUHSC_02723, SAOUHSC_01311, and vraS . Decreased transcription was observed in genes involved in toxin production and stress response ( hlgA, SAOUHSC_01110, hly, hlgB, efb, and hlgC ). All changes in transcription were confirmed using real-time qPCR. The membrane potential of S. aureus treated with 500 mg/L EGCg markedly decreased, indicating that EGCg damaged the cell membrane. Conclusions: S. aureus increases the transcription of genes involved in membrane transport to recover membrane function. EGCg can potentially serve as a natural antibacterial agent to control the growth and toxin production of S. aureus .